Fiscal and non-fiscal determinants behind the creation of new work places in the private sector - a review of chosen areas - Milewska, Anna (Management and Administration Journal, 2020)
The author of this article presents fiscal and non-fiscal factors that determine the creation of new work places in the private sector. To help explain this topic it was important to study the legal acts and available literature as well as use of other qualitative theoretical methods such as: analysis, synthesis, comparison, generalization, deductive and inductive reasoning methods. This resulted in distinguishing public levies which are significant to determine the costs of employment. These costs mainly include contributions to the pension (retirement insurance, disability insurance premium and work accident insurance) as well as to the Labour Fund. In the following part the author presents the specifics of the human and social capital, employee’s competencies, globalisation and generational differences that impact the current job market. The outcome of this study concludes that employment costs have remained fairly stable for the last few years (the last major increase of employment contributions took place in 2012). Nonetheless, a growing scarcity of human resources, especially generation Y, has become the biggest challenge.